2021
DOI: 10.3390/math9070763
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive State-Quantized Control of Uncertain Lower-Triangular Nonlinear Systems with Input Delay

Abstract: In this paper, we investigate the adaptive state-quantized control problem of uncertain lower-triangular systems with input delay. It is assumed that all state variables are quantized for the feedback control design. The error transformation method using an auxiliary time-varying signal is presented to deal with the compensation problem of input delay. Based on the error surfaces with the auxiliary variable, a neural-network-based adaptive state-quantized control scheme is constructed with the design of the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…In the work [30], it is demonstrated that the Wirtinger inequality encompasses Jensen's inequality and facilitates, if it is used, the reduction of conservatism. The approach from [31] allows an extension to various practical systems, such as jet engines, flight systems and robots, if the mathematical models are presented in a lower triangular form. Finally, in a recent paper [32], the probabilistic control of discrete-time stochastic systems with multiple control inputs and state delays was considered.…”
Section: Introductionmentioning
confidence: 99%
“…In the work [30], it is demonstrated that the Wirtinger inequality encompasses Jensen's inequality and facilitates, if it is used, the reduction of conservatism. The approach from [31] allows an extension to various practical systems, such as jet engines, flight systems and robots, if the mathematical models are presented in a lower triangular form. Finally, in a recent paper [32], the probabilistic control of discrete-time stochastic systems with multiple control inputs and state delays was considered.…”
Section: Introductionmentioning
confidence: 99%